Increasing Understanding of the Urgency of Trade Secrets for Business to Gen Z at SMAN 1 Semarang - Irawaty, Irawaty; Fidiyani, Rini; Mukminto, Eko; Widhiyanto, Widhiyanto; Hanum, Holy Latifah (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement), 2023)
Trade secrets are one of Intellectual Property forms that is considered most valuable in business. However, result of research shows that trade secrets are not as famous as patents, copyrights, and trademarks. In Indonesia, trade secrets Act has been established by the government since 2000. Following the fact that trade secrets are still not commonly understood by societies, thus it is important to educate societies about trade secrets. This community service selected to educate gen Z in SMAN 1 Semarang since knowledge to trade secrets should be understood as early as possible. Nevertheless, it is worth to note that there are some reasons to conduct the community service in the school, two of them are SMAN 1 Semarang is one of the best high schools in the city and some students have achieved some prestigious awards in research. The methods in carrying the community service were by delivering important points on trade secrets, discussion session, and post-test. Based on the post-test answers, almost all students understood the urgency of trade secrets for business and stated that the event was useful.